The Algorithm of Digital Technology for Communication - Rr Dinar Soelistyowati; Sri Ekowati (Jurnal Penelitian Pendidikan IPA, 2025)
This paper explores effectively utilize digital technology for a campaign or communication. A solid algorithm-driven approach can be implemented to ensure data-driven decisions, targeted messaging, and high engagement. Citizens can easily actively disseminate political issues through existing social media platforms. This research uses descriptive research with a qualitative approach with a literature study approach. The data collection technique in this research is to conduct a literature search that is current and compatible with the research theme.  The results of the study show that social media plays an important role in political participation in the digital era. Digital technology can also trigger opinion polarization.  Political participation in the digital era has positive impacts and real challenges that must be addressed properly and wisely. Awareness of digital literacy and being critical are the main keys to maintaining inclusive political participation in this digital age. Collect data from social media, surveys, website analytics, and polling. Ensure that the data collected adheres to privacy and data protection regulations. Use machine learning algorithms like k-means clustering to segment the audience based on demographic, psychographic, geographic, and behavioral factors. Based on the segmentation, create voter personas (such as "young urban voters" or "female first-time voters") to tailor campaign messages effectively. Use natural language processing (NLP) to analyze sentiments around PSI and specific campaign topics. This will help identify areas of improvement and potential voter concerns. Employ tools like IBM Watson or Google Cloud Natural Language to monitor conversations around key issues and track public sentiment in real time.